Mutations in FIGLA Associated With Premature Ovarian Insufficiency in a Chinese Population - Mei, Libin; Huang, Yanru; Wu, Xiaoling; He, Huang; Ye, Ronghui; Ma, Jinxiu; He, XueMei; Shi, Yuhua; Li, Ping (Frontiers in Medicine, 2021)
Objective: Premature ovarian failure (POF) is one of the most common reproductive endocrinological causes of infertility in women of child-bearing age. The purpose of this study was to identify FIGLA gene mutations in Chinese patients with POF and to investigate the underlying mechanism. Methods: A total of 113 patients with idiopathic POF and 100 healthy controls were recruited for the analysis of FIGLA variants. Based on common identification of mutations in the FIGLA, wild-type and mutant plasmids were constructed and transfected into HEK293 cells. Luciferase reporter genes were used to determine the effect of wild-type and mutant FIGLA genotypes on the transcriptional activity of its downstream targets, the zona pellucida glycoprotein genes ZP1, ZP2, and ZP3. Chromatin immunoprecipitation was used to determine the level of binding between wild-type and mutant FIGLA with the ZP1, ZP2, and ZP3 promoters. Results: Three different FIGLA mutations were identified in four patients with POF. Two patients carried the mutation c.11C>A (p.A4E), and the other two patients respectively carried the mutation c.625G>A (p.V209I) and c.84C>A (p.D28E). The luciferase reporter assay indicated that ZP1, ZP2, and ZP3 transcriptional activities were significantly reduced in individuals with FIGLA mutations. Chromatin immunoprecipitation indicated that the FIGLA mutation significantly decreased binding with the ZP1, ZP2, and ZP3 promoters. Conclusion: FIGLA mutation affects gene transcriptional regulation of its downstream target genes ZP1, ZP2, and ZP3, highlighting a new candidate genetic factor that causes POF. Our study demonstrates that FIGLA has a regulatory effect on reproduction-specific genes, thereby providing a basis for elucidating the specific regulatory mechanism of FIGLA in germ cell growth and development.